PKM Kewirausahaan Lumpia Aplous - Ratnah S; Nahriana Nahriana; Nur Arisah; Nurjannah Nurjannah; Mustari Mustari (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
Lumpia is a type of food that is very popular in Asia, especially in Indonesia and the Philippines. This food consists of a thin skin filled with various ingredients, such as vegetables, meat, or sweet ingredients. The history of spring rolls can be traced back to Chinese cultural influence in Southeast Asia, where spring rolls were known as "spring rolls". Thin and crispy spring roll skin is made from flour mixture mixed with water and a little oil, then fried until crispy. The methods used in this activity include lectures, questions and answers or discussions, and training. The results obtained are that Lumpia with Chocolatos filling offers several advantages compared to conventional spring rolls. Apart from the pleasant sweet taste, these spring rolls are also easy to make and are liked by all ages. Its popularity is increasing thanks to the ease of obtaining the ingredients and its ability to be made into an attractive snack or dessert. This innovation shows how traditional culinary delights can develop and adapt to modern tastes, creating new opportunities in the snacks and snacks industry.